Rancang Bangun Sistem Informasi Rekrutmen Karyawan Berbasis Web pada PT Megah Perkasa Teknologi - Martini Martini; Agustiena Merdekawati (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2020)
Admission of new employees is undoubtedly one of the programs for the company to gethuman resources who have the potential and qualifications according to company needs. Thepurpose of this study is to design an employee recruitment system at PT Megah PerkasaTeknologi that still utilizes social media and verbal communication from one person toanother so that only a few are aware of the recruitment needs. HRD still records and selectsincoming files both obtained via e-mail and sent through the delivery service. Therefore weneed a web-based employee recruitment system that can provide more comprehensiveinformation to the public, especially those who are looking for work. The system designedusing the Unified Modeling Language, and software developers use the Waterfall model withthe PHP and MySQL programming languages. The results of this study indicate that employeerecruitment information disseminated to the community and its requirements. Applicants canonly apply for one position in the employee recruitment period with the ease of filling outapplications. Also, file selection becomes more accessible and faster because the applicant isonly required to apply according to the desired application position. So with this web-basedrecruitment system, the HRD team's performance is expected to be more productive andefficient at every stage from file receipt, written test, interview test, to decision making.